Search for strong gravity signatures in same-sign dimuon final states using the ATLAS detector at the LHC - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acharya, B; et al. (Elsevier, 2012)
A search for microscopic black holes has been performed in a same-sign dimuon final state using 1.3 fb−1 of proton–proton collision data collected with the ATLAS detector at a centre of mass energy of 7 TeV at the CERN Large Hadron Collider. The data are found to be consistent with the expectation from the Standard Model and the results are used to derive exclusion contours in the context of a low scale gravity model.